PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KONSTRUKTIVISTIK PESERTA DIDIK PADA PEMBELAJARAN IPA KELAS VI DI MADRASAH IBTIDAIYAH - Lilla Septiliana; Andi Prastowo (Mentari : Journal of Islamic Primary School, 2023)
This study aims to describe the application of the contextual teaching and learning (CTL) approach in improving students' constructivist thinking skills in class VI science learning at Madrasah Ibtidaiyah. This study used a qualitative method with descriptive qualitative research. The primary data source was obtained from the teacher. Data collection techniques in this study used observation, interviews and documentation. The data analysis technique used in this study is data reduction, data presentation and conclusion. With the results of research regarding the application of the Contextual Teaching and Learning (CTL) approach to improve the constructivist thinking skills of students in science learning class VI of Madrasah Ibtidaiyah, that science learning includes three stages namely planning, implementation and evaluation and in this study the results were obtained by increasing the ability Constructive thinking of students in science learning with the Contextual Teaching and Learning approach at Madrasah Ibtidaiyah is based on the teacher's competency in managing the class first starting from asking questions, and learning media, the teacher in optimizing all students' abilities to be able to participate actively in learning through providing motivation to students, there are also efforts to overcome obstacles from the ineffectiveness of the CTL learning approach by increasing the percentage of time for teachers